1989
DOI: 10.1111/j.1469-8986.1989.tb01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep on the Night Shift: 24‐Hour EEG Monitoring of Spontaneous Sleep/Wake Behavior

Abstract: The present study sought to objectively describe the spontaneous sleep/wakefulness pattern of shift workers during a 24-hour period. Portable Medilog tape-recorders were used for ambulatory EEG monitoring of 25 male papermill workers (25-55 years) during days with night and afternoon work. The results showed that sleep after night work was two hours shorter than after afternoon work. The sleep reduction affected mainly Stage 2 and REM sleep while slow wave sleep was unchanged. In connection with night work 28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
78
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(97 citation statements)
references
References 28 publications
12
78
0
7
Order By: Relevance
“…The lack of increased total amounts of SWS and SWE in night-shift sleep was expected from prior studies of shift workers (1)(2)(3)(4)(5)(6)(7)(8) . Admittedly, at first thought, one might expect increased slow-wave levels because of the prior sleep loss involved and its expected effects on SWS or SWE (10,21,23).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The lack of increased total amounts of SWS and SWE in night-shift sleep was expected from prior studies of shift workers (1)(2)(3)(4)(5)(6)(7)(8) . Admittedly, at first thought, one might expect increased slow-wave levels because of the prior sleep loss involved and its expected effects on SWS or SWE (10,21,23).…”
Section: Discussionmentioning
confidence: 67%
“…Mean and standard error (SE) per non-REM-REM sleep cycle for sleep parameters in connection with afternoon, morning , and night workshifts. a (SWE = slow-wave energy , SWA = slow-wave activity, SWS = slow-wave sleep , REM = rapid-eye- previous studies (1)(2)(3)(4)(5)(6)(7)(8). In other words, sleep after the night shift was reduced by more than 2 h, the loss affecting stage 2 and REM sleepmainly and SWS marginally.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Research has also found negative associations between rotating schedules and employee productivity, safety and accident-proneness (Johnson et. al, 1981;Regestein and Monk, 1991), reduced total sleep and poorer sleep quality (Torsvall, et. al., 1989).…”
Section: Work Schedulesmentioning
confidence: 99%
“…In contrast, descriptions of real sleep episodes during nightwork outside any specific experiment and without any formal authorization are scarce (10).…”
mentioning
confidence: 99%